2005
DOI: 10.1177/112972980500600206
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Low-Dose Alteplase for Treatment of Hemodialysis Catheter Occlusions

Abstract: Low dose alteplase 1 mg/lumen successfully treated occlusion of permanent hemodialysis catheters, with a resulting cost reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…The reported incidence of catheter dysfunction ranges from 5 to 80%, depending on the definition, population, and catheter characteristics (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). The interpretation of studies that use blood flow as a measure of catheter dysfunction are challenging without knowledge of blood pump setting, use of average versus episodic measures of blood flow, percentage of recirculation, and other dialysis variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported incidence of catheter dysfunction ranges from 5 to 80%, depending on the definition, population, and catheter characteristics (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). The interpretation of studies that use blood flow as a measure of catheter dysfunction are challenging without knowledge of blood pump setting, use of average versus episodic measures of blood flow, percentage of recirculation, and other dialysis variables.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of CVC dysfunction varies across the literature and includes variable rates of blood flow ranging from Ͻ100 to 350 ml/min (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). The NKF-DOQI vascular access guideline defines CVC dysfunction as failure to attain and maintain extracorporeal blood flow that is sufficient to perform HD without significantly lengthening the HD treatment and considered insufficient extracorporeal blood flow to be Ͻ300 ml/min (6).…”
mentioning
confidence: 99%
“…A single instillation of low-dose alteplase with a 30-minute dwell restored or maintained Qb Ͼ300 without line reversals in 36 of 50 (72%) patients, with a second instillation restoring patency for a further four patients (40 of 50 patients; 80%) (59). The majority of patients (70%) required additional intervention within the 4-month follow-up of further alteplase instillation (62%; median time to next exposure 14 days) and/or radiologic intervention (59).…”
Section: Efficacy Of Lytic Therapy In Catheter Clearancementioning
confidence: 99%
“…Two studies have demonstrated efficacy for alteplase 1 mg/ml instillation in restoring the patency of occluded HD catheters (59,60). A single instillation of low-dose alteplase with a 30-minute dwell restored or maintained Qb Ͼ300 without line reversals in 36 of 50 (72%) patients, with a second instillation restoring patency for a further four patients (40 of 50 patients; 80%) (59).…”
Section: Efficacy Of Lytic Therapy In Catheter Clearancementioning
confidence: 99%
“…In fact, it is common to find a significant overall effect size in a meta‐analysis of studies that, as single studies, had no effect. In a prospective study that was characterized by a relatively small sample, Haymond et al . reported no difference between 1.0 and 2.0 mg tPA, and suggested that 1.0 mg tPA dose may be as efficacious as 2.0‐mg dose.…”
Section: Introductionmentioning
confidence: 99%